2018
DOI: 10.1111/exd.13754
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo fluorescence confocal microscopy for intraoperative, real‐time diagnosis of cutaneous inflammatory diseases: A preliminary study

Abstract: Ex vivo fluorescence confocal microscopy (FCM) is an innovative imaging tool that can be used intraoperatively to obtain real-time images of untreated excised tissue with almost histologic resolution. As inflammatory diseases often share overlapping clinical features, histopathology evaluation is required for dubious cases, delaying definitive diagnoses, and therefore therapy. This study identifies key-features at ex vivo FCM for differential diagnoses of cutaneous inflammatory diseases, in particular, psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
(43 reference statements)
0
30
1
1
Order By: Relevance
“…Da entzündliche Erkrankungen häufig überlappende klinische Merkmale aufweisen, ist in zweifelhaften Fällen eine histopathologische Bewertung häufig erforderlich, um die endgültigen Diagnosen und damit die Therapie nicht zu verzögern. Eine retrospektive Studie zur Identifizierung der Schlüsselmerkmale für die Differenzialdiagnose von entzündlichen Hauterkrankungen, insbesondere Psoriasis, Ekzem, Lichen planus und diskoidem Lupus erythematodes in der ex vivo KLM analysierte und korrelierte die ex vivo KLM mit histologischen Untersuchungen der relevanten Diagnosen, um die Übereinstimmung und das für die korrekte Diagnose erforderliche Fachwissen zu bewerten [10]. Hier zeigte sich, dass die ex vivo KLM in den meisten Fällen die Unterscheidung der wichtigsten Entzündungsmerkmale ermöglichte und eine erhebliche Übereinstimmung mit den histopathologischen Diagnosen ergab [10].…”
Section: Psoriasis Ekzem Lichen Planus Und Lupusunclassified
“…Da entzündliche Erkrankungen häufig überlappende klinische Merkmale aufweisen, ist in zweifelhaften Fällen eine histopathologische Bewertung häufig erforderlich, um die endgültigen Diagnosen und damit die Therapie nicht zu verzögern. Eine retrospektive Studie zur Identifizierung der Schlüsselmerkmale für die Differenzialdiagnose von entzündlichen Hauterkrankungen, insbesondere Psoriasis, Ekzem, Lichen planus und diskoidem Lupus erythematodes in der ex vivo KLM analysierte und korrelierte die ex vivo KLM mit histologischen Untersuchungen der relevanten Diagnosen, um die Übereinstimmung und das für die korrekte Diagnose erforderliche Fachwissen zu bewerten [10]. Hier zeigte sich, dass die ex vivo KLM in den meisten Fällen die Unterscheidung der wichtigsten Entzündungsmerkmale ermöglichte und eine erhebliche Übereinstimmung mit den histopathologischen Diagnosen ergab [10].…”
Section: Psoriasis Ekzem Lichen Planus Und Lupusunclassified
“…Preliminary research into FCM as a diagnostic tool for other visceral organ cancers seems promising . Furthermore, it showed to be a promising tool for diagnosis of cutaneous inflammatory skin lesions .…”
Section: Introductionmentioning
confidence: 99%
“…So far, ex vivo CLSM has been mainly used in the intra‐ and postoperative assessment of skin tumours, the control of surgical skin margins and as an assistive method for Mohs microscopic surgery . A few studies have reported that ex vivo CLSM examination on freshly excised samples may also be helpful in the rapid diagnosis of inflammatory and infectious skin lesions . Recently, our group combined ex vivo CLSM examination with fluorescent‐labelled antibody staining in the tissue sections of patients with melanoma, BCC and cutaneous vasculitis, and showed that ex vivo CLSM may have potential as an alternative method in immunofluorescent examination of skin.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] A few studies have reported that ex vivo CLSM examination on freshly excised samples may also be helpful in the rapid diagnosis of inflammatory and infectious skin lesions. [11][12][13][14][15] Recently, our group combined ex vivo CLSM examination with fluorescent-labelled antibody staining in the tissue sections of patients with melanoma, BCC 2 and cutaneous vasculitis, 16 and showed that ex vivo CLSM may have potential as an alternative method in immunofluorescent examination of skin.…”
Section: Introductionmentioning
confidence: 99%